Development of Catch-up TV Application on Internet TV Platform for RTSP/RTMP Streaming Protocol - I Ketut Agung Enriko (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
With the proliferation of video streaming services, now internet TV has become a popular service on the Internet. Catch-up TV is an attractive service in internet TV, where user who misses a live programme can watch it later. Meanwhile, not all streaming protocols, by default, are able to support catch-up TV application. This paper explains how to develop catch-up TV application in RTSP/RTMP streaming protocol, by doing shell-script programming and using Wowza streaming engine, on Linux-based streaming server. The research result has been implemented in UseeTV, one of the largest commercial internet TV service in Indonesia.